Political Economy of the Wheat Sector in Uzbekistan Seed Systems, Variety Adoption and Impacts - Yigezu, Yigezu; Bishaw, Zewdie; Niane, Abdoul Aziz; Nurbekov, Aziz (International Center for Agricultural Research in the Dry Areas, 2022)
Agriculture plays an important role in the economy of Uzbekistan contributing 16% to GDP and 44% to employment. Uzbekistan has a land area of 44.8 million ha, of which about 4.5 million ha is arable, and 4 million ha is irrigated. Main cultivated crops are cotton, wheat, barley, rice, maize, potatoes, and horticultural crops (vegetables and fruits). The population of Uzbekistan was estimated at 34 million in 2019 and continues to grow at a rate of 1.67% per year (WB, 2019). Currently, an estimated 18 million people live in rural areas, most of which draw their livelihoods from agriculture. During the Former Soviet Union (FSU) era, Uzbekistan was a major producer of cotton, vegetables, and fruits. About 70% of irrigated land was devoted to cotton production, while fodder crops (alfalfa, rye, barley, and maize) were grown in rotation with cotton and supported limited livestock production. Wheat, one of the key food security crops, was mostly imported from other regions of the FSU, with local production meeting only 20% of domestic demand. After its independence in 1991, Uzbekistan’s access to strategic food imports became less secure due to the abolition of the centrally coordinated commodity supply and subsidy systems between Russia and its Soviet Socialist Republics. Subsequent structural adjustments by the former Soviet republics made the contracting system less reliable and reduced regional trade. As a landlocked country with limited access to international markets, it became very important for Uzbekistan to ensure its food security through domestic production. Over the decades, Uzbekistan’s agricultural policy was characterized by full Government control over agricultural production and marketing. Land is owned by the Government as enshrined in the Constitution. The Government distributes land to farmers and determines the agricultural commodities to be grown under Government quotas (public procurement contracts). Two of the Government’s major goals were to increase the much-needed foreign exchange revenue through the export of cotton, and to increase self-sufficiency in wheat production - thereby reducing dependence on imports. However, this inadvertently led to monoculture of cotton and wheat in most of the country.